2014
DOI: 10.1080/15321819.2013.848813
|View full text |Cite
|
Sign up to set email alerts
|

Over-Expression of Egfr is Closely Correlated to Poor Prognosis in Tunisian Patients with Non-Small Cell Lung Adenocarcinoma

Abstract: We studied epidermal growth factor receptor (EGFR) expression profile with the aim of an individualized therapy for patients with non-small cell lung cancer (NSCLC) from whom tumor materials are not sufficient for molecular investigations. Using immunohistochemistry, we found a markedly increased EGFR expression with significant difference in term of intensity and distribution from normal mucosa to primary tumors (p < 0.05). Furthermore, patients with EGFR positive tumors had significantly shorter survival tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…The patients in the current study did not demonstrate any significant association between serum EGFR mRNA expression and various clinical characteristics such as age, gender, smoking status, disease stage or (Suwinski et al, 2012;Arfaoui et al, 2014) smoking status, (Zhuo et al, 2014Arfaoui et al, 2014) and advanced disease stage, (Sun et al, 2015;Arfaoui et al, 2014;Liang et al, 2012;Traynor et al, 2013) while several others have not. (Hirschet al, 2003;Brabender et al, 2001;Han et al, 2015;Liang et al, 2010).…”
Section: Discussioncontrasting
confidence: 49%
“…The patients in the current study did not demonstrate any significant association between serum EGFR mRNA expression and various clinical characteristics such as age, gender, smoking status, disease stage or (Suwinski et al, 2012;Arfaoui et al, 2014) smoking status, (Zhuo et al, 2014Arfaoui et al, 2014) and advanced disease stage, (Sun et al, 2015;Arfaoui et al, 2014;Liang et al, 2012;Traynor et al, 2013) while several others have not. (Hirschet al, 2003;Brabender et al, 2001;Han et al, 2015;Liang et al, 2010).…”
Section: Discussioncontrasting
confidence: 49%
“…These studies investigated the role of angiogenic pathway genes like EGFR and MMP-3 in lung carcinogenesis ( 292 297 ). The expression of EGFR was associated with poor prognosis, and the frequency of the mutations observed in Tunisian and Moroccan patients was similar to those of Europeans ( 294 , 296 , 298 ). However, Dhieh et al ( 292 ) found that abnormal p53 expression in these patient populations was more frequent than in Europeans.…”
Section: Resultsmentioning
confidence: 62%
“… 5 EGFR overexpression is associated with tumor invasion, metastasis, cycle distribution, apoptosis, and angiogenesis, 6 and is also responsible for poor prognosis and radiation resistance. 7 , 8 EGFR inhibition is a potential method that may enhance radiosensitivity.…”
Section: Introductionmentioning
confidence: 99%